2019
DOI: 10.1002/nme.6096
|View full text |Cite
|
Sign up to set email alerts
|

Homogenized enriched model for blast wave propagation in metaconcrete with viscoelastic compliant layer

Abstract: Summary In this contribution, a reduced‐order homogenization approach is adopted and extended to incorporate the linear viscoelasticity effect. A homogenized enriched model emerges from the homogenization framework, which is utilized here for the analysis of blast wave propagation in metaconcrete with linear viscoelastic compliant layer(s). A semidiscrete equation of motion for the unit cell is first extracted for micro‐macro transition, through a series of transformations to effect the periodic boundary condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Numerical studies have been carried out demonstrating the reduction for both longitudinal and transverse vibration modes of metaconcrete [12][13][14][15][16][17][18][19] , in addition to experimental validations endorsing this behavior [20][21][22] , even if the inclusions are dispersed in a random 23,24 or quasi-random arrangement 25 . Furthermore, a simplified analytical model for metaconcrete filled with randomly distributed resonators has been proposed 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies have been carried out demonstrating the reduction for both longitudinal and transverse vibration modes of metaconcrete [12][13][14][15][16][17][18][19] , in addition to experimental validations endorsing this behavior [20][21][22] , even if the inclusions are dispersed in a random 23,24 or quasi-random arrangement 25 . Furthermore, a simplified analytical model for metaconcrete filled with randomly distributed resonators has been proposed 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2021bXu et al ( , 2022a conducted impulsive load experiments to investigate the influence of different kinds of aggregates and bandgaps on the stress wave mitigation of metacnocrete rod. Tan et al (2019) developed a homogenized enriched model for analyzing the blast wave propagation in metaconcrete with viscoelastic compliant layer. Liu et al (2021Liu et al ( , 2022 designed single-resonator and double resonator metconcrete spcimen and studied the vibration attenuation effect of metaconcrete specimen by frequency sweeping vibration experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The effects on attenuation bands of inclusion shape, size, and volume fraction and the sensitivity to material properties were investigated numerically by Xu et al [11]. Enriched homogenization techniques to describe the effective behavior of metaconcrete with viscous inclusion coatings have been introduced by Tan et al [12] as a promising approach for the analysis of large structures. Numerical and experimental tests by Barnhart et al [13] on an elastic metamaterial containing five-layer spherical resonators demonstrated the possibility of obtaining two attenuation regions that can be combined or overlapped by suitably tuning geometric and material parameters.…”
Section: Introductionmentioning
confidence: 99%